Effects of IL-6, IL-10 and TGF-β on the expression of survivin and apoptosis in nasopharyngeal carcinoma TW01 cells - Poh, Y.W.; Gan, S.Y.; Tan, E.L. (Experimental Oncology, 2012)
The aim of this study is to investigate whether IL-6, IL-10 and TGF-β are able to confer resistance to apoptosis in nasopharyngeal carcinoma cells by upregulating the expression of survivin. Methods: The human nasopharyngeal carcinoma cell line TW01 (WHO NPC Type I) was cultured in DMEM-F12 Ham medium containing 10% FBS in a humidified atmosphere of 5% CO2 and 37◦C and treated with different concentrations of IL-6, IL-10 and TGF-β. Survivin mRNA expression was measured by real-time quantitative PCR and Western blot. Apoptosis was determined based on the assay for caspase-3 activity. Results: Of all the cytokines tested, only TGF-β (10 pg/mL) induced the over-expression of survivin at a significant level and this correlated with resistance to apoptosis (p ≤ 0.05). To confirm if survivin is responsible for resistance to apoptosis, YM155 which is a survivin inhibitor was used and the results showed that YM155 abrogated the protective effect of TGF-β. Interestingly, IL-10 did not significantly alter the expression of survivin. Conclusions: We conclude that TGF-β up-regulates the expression of survivin leading to the resistance to apoptosis in NPC TW01 cells.